Emerging applications of aerogels in textiles - Steven J. McNeil (Elsevier, 2022)
The high specific surface areas and porosities of aerogels can impart desirable properties to textiles. The most established application of aerogels in textiles is the enhancement of thermal insulation and this has been the subject of some excellent reviews. This review, for the first time, discusses the other applications of aerogels in textiles and considers enhancements in mechanical and acoustic properties, water repellency, permeability to air and water, acoustics, protection from radiation, chemicals and fire, and the remediation of textile processing effluent. These discussions are underpinned by the various approaches and materials employed for preparing aerogels, and the methods for incorporating them into textiles. Future prospects for aerogels in textiles are reviewed, and it is likely that innovations in aerogels driven by the energy storage, aerospace, and medical technology sectors such as lower production costs and greater use of biopolymers and hybrids, will underpin innovation in textile-aerogels. It is hoped this review will inspire collaboration between researchers in the fields of aerogels and textiles.